Requirement Elicitation Model (REM) in the Context of Global Software Development - Muhammad Yaseen; Umar Farooq (Institute of Advanced Engineering and Science, 2018)
Requirement elicitation is difficult and critical phase of requirement engineering and the case is worst in global software development (GSD). The study is about requirement elicitation in the context of GSD. Development of requirement elicitation model (REM) which can address the factors that have positive impact and the factors that have negative impact during elicitation in GSD. The propose model will give solutions and practices to the challenges during elicitation. Systematic literature review (SLR) and empirical research study will be used for achieving the goals and objectives. The expected results of this study will be REM that will help vendor organizations for better elicitation during GSD.